1962
DOI: 10.1680/geot.1962.12.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to the Use of Effective Stresses in Partly Saturated Soils

Abstract: Synopsis Terzaghi's effective stress principle may be stated in the form of two propositions:— (i) Changes in volume and shearing strength of a soil are due exclusively to changes in effective stress. (ii> The effective stress σ′ in a soil is defined as the excess of the total applied stress σ over the pore pressure u. The validity of this principle for fully saturated soils is now well established and has proved invaluable in the prediction of the behaviour of such soils. In recent years workers have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
196
0
19

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(223 citation statements)
references
References 5 publications
8
196
0
19
Order By: Relevance
“…Experimental investigations (Jennings and Burland, 1962) have shown that it may depend on the saturation S r,w but there is non-unique relation v À S r,w for a given soil sample with different void ratios.…”
Section: Stress State Variablesmentioning
confidence: 99%
“…Experimental investigations (Jennings and Burland, 1962) have shown that it may depend on the saturation S r,w but there is non-unique relation v À S r,w for a given soil sample with different void ratios.…”
Section: Stress State Variablesmentioning
confidence: 99%
“…Also, the compression curves, once the wetting is completed, follow a unique path for saturated conditions (path DF after wetting 2 follows the saturated compression curve BDF). Experimental results which favour this uniqueness have been reported by Jennings and Burland (1962) and Blight (1965) for collapsing sands, by Erol and El-Ruwaih (1982) testing loess and by Maswoswe (1985) in the case of a low plasticity sandy clay.…”
Section: Parameters Of the Model And Their Determinationmentioning
confidence: 67%
“…Second, it is believed that combining macroscopic and microscopic stresses into a single equation is incorrect (Burland 1965). Finally, it was shown that on wetting (i.e., reducing suction), unsaturated soil samples collapsed during consolidation tests (Jennings and Burland 1962). Based on Equation (2-22), the effective stress should decrease on reducing the suction and unsaturated soil samples should have expanded.…”
Section: (2-23)mentioning
confidence: 99%